Evaluation of Shape Recovery Performance of Shape Memory Polymers with Carbon-Based Fillers - Choi, Sungwoong; Jang, Seongeun; Yoo, Seung Hwa; Lee, Gyo Woo; Choi, Duyoung (MDPI Open Access Publishing, 2024)
This study focuses on enhancing the thermal properties and shape recovery performance of shape memory polymers (SMPs) through the application of carbon-based fillers. Single and mixed fillers were used to investigate their effects on the glass transition temperature (Tg), thermal conductivity, and shape recovery performance. The interaction among the three-dimensional (3D) structures of mixed fillers played a crucial role in enhancing the properties of the SMP. These interactions facilitated efficient heat transfer pathways and conserved strain energy. The application of mixed fillers resulted in substantial improvements, demonstrating a remarkable 290.37% increase in thermal conductivity for SMPCs containing 60 mu m carbon fiber (CF) 10 wt% + graphite 20 wt% and a 60.99% reduction in shape recovery time for SMPCs containing CF 2.5 wt% + graphite 2.5 wt%. At a content of 15 wt%, a higher graphite content compared to CF improved the thermal conductivity by 37.42% and reduced the shape recovery time by 6.98%. The findings demonstrate that the application of mixed fillers, especially those with high graphite content, is effective in improving the thermal properties and shape recovery performance of SMPs. By using mixed fillers with high graphite content, the performance of the SMP showed significant improvement in situations where fast response times were required.